Recognition and Virtualization in Frankfurt School - Al Ahmad, Ahmad; Nassar, Dua’a; Al Dababsa, Suzan; Issa, Theodora; Issa, Tomayess (Dirasat: Human and Social Sciences, 2025)
Objectives: This research examines the concept of recognition according to the Frankfurt School of philosophy, focusing on first-generation thinkers like Max Horkheimer, Theodor Adorno, and Herbert Marcuse. It explores the origins, significance, and development of the concept, linking it to postmodern philosophy and comparative studies with the Frankfurt School. The analysis also includes Jürgen Habermas and Axel Honneth’s views on recognition in the virtual world. Method: The paper follows an analytical approach by examining Habermas and Honneth’s perspectives on recognition in the virtual realm, using secondary data and literature reviews. Results: The study highlights the importance of recognition in virtual spaces, demonstrating that these environments enable participation and expression, expanding the scope of recognition within virtual interactions. The virtual world offers individuals greater opportunities for self-expression and identity formation. Conclusions: The study emphasizes the role of society as a broad communicative environment, in line with Frankfurt School philosophers. It also underscores that the virtual space functions as a human environment that empowers individuals, enhancing their participation. Using technology for decision-making and expression broadens the application of recognition to include the virtual realm.